Interrelationships of Biochemical Parameters in Milks from Machine Milking - Yildirim, S.; Cimen, M. (Asian Journal of Chemistry, 2010)
The aim of this research is to investigate the relationships between biochemical components in milks from machine milking. The data was obtained from DIMES Company. The milk component levels in this study are consistent with normal values for cows. There was positive correlation between solids and total fat (r = 0.59; p < 0.01) and between solids and milk acidity (sH) (r = 0.75; p < 0.01). But, no relationship was found between solids and pH. There was no correlation between pH and sH levels in machine milking. The fat has a higher correlation with sH (r = 0.64; p < 0.01). This should be useful in calculating the quantity of fat in milk for cheese-making. Relationships between biochemical parameters are also useful in studying the physiology of milk production. Further researches are needed to confirm the findings obtained from machine milking cows in this study.